Decolonizing Gender Roles: Women’s Embedded Agency in Family and Livelihood Systems in Nolloth Village, Indonesia - Feky Manuputty; Anike Jacomina M. Manuputty (Baileo: Jurnal Sosial Humaniora, 2026)
This article examines the decolonization of gender roles by analyzing women’s embedded agency within family and livelihood systems in Nolloth Village, Indonesia. Challenging dominant global narratives that portray women as confined to domestic and marginalized roles, the study highlights the relational and context-specific dynamics of gender in a Global South island society. Using a qualitative intrinsic case study design, data were collected through in-depth interviews, participant observation, and documentation of everyday economic practices among fishing and farming households. Thematic and interpretive analysis reveals that women occupy strategic positions across the entire production chain. In fisheries, they manage processing, distribution, and market exchange, while in subsistence agriculture they participate from cultivation to harvest. These roles are not perceived as subordination but as integral to collective household responsibility, providing women with social recognition and decision-making influence. The findings advance the concept of embedded agency, demonstrating how women’s power is enacted through integration within social and economic structures rather than overt resistance. By challenging rigid dichotomies such as domestic versus public and productive versus reproductive labor, this study contributes to decolonial sociology and feminist political economy, offering a context-sensitive framework for understanding gender in the Global South.